Erosion and Sedimentation Rate Analysis to Determine the Useful Life of Meninting Dam - Ida Bagus Andrew Widyantara; I Wayan Yasa; Yusron Saadi (Postgraduate, University of Mataram, 2026)
Meninting Dam, constructed in 2019 in West Lombok Regency, is a newly built reservoir that is vulnerable to sedimentation caused by land erosion in its upstream catchment area. This study aims to estimate the erosion rate, sedimentation rate, and predicted service life of the Meninting Dam as a basis for early sediment management planning. Erosion was calculated using the Modified Universal Soil Loss Equation (MUSLE), while sedimentation was estimated using the Sediment Delivery Ratio (SDR) based on the Boyce (1975) method, integrated with spatial analysis using QGIS. The results show that the erosion rate in the Meninting Dam catchment area reaches 884,467.83 tons/year, producing a sedimentation rate of 40,526.39 m³/year and an estimated dam service life of approximately 45 years. These findings indicate that erosion-induced sedimentation poses a significant long-term risk to the storage capacity of the Meninting Dam and highlight the importance of early erosion control and sediment management strategies for newly constructed reservoirs.